Legal Protection for Children Taken by Their Mothers as Convicts in Correctional Institutions - Januar Akbar Wibisono (Strata Law Review, 2023)
This research aimed to address the problem of how to fulfil the rights of children brought by their mothers into correctional institutions and the form of protection for the rights of children brought by their mothers as convicts into correctional institutions. This research method is is a document (normative) study. The results of this research show that according to Article 20 paragraph (4) Government Regulation Number 32 of 1999, it is determined that a child whom their mother brings into prison must only reach the age limit of 2 (two) years. This is inappropriate if it is linked to the principle of The best interests of the child and the mandate of Law of the Republic of Indonesia Number 4 of 1979 concerning Child Welfare. The presence of parents beside the child is not enough to only reach the age of two years. Above the age of two years, children still need a mother figure by their side. A special study is required regarding the age limit for a child to be in the care of their mother in prison. This is a consideration for lawmakers to formulate regulations in children's best interests to separate them from other prisoners.